Mobility of charge carriers in self-assembled monolayers - Fu, Zhihua; Ladnorg, Tatjana; Gliemann, Hartmut; Welle, Alexander; Bashir, Asif; Rohwerder, Michael; Zhang, Qiang; Schüpbach, Björn; Terfort, Andreas; Wöll, Christof (Beilstein Journal of Nanotechnology, 2019)
We present a new approach to study charge transport within 2D layers of organic semi-conductors (OSCs) using atomic force microscopy (AFM)-based lithography applied to self-assembled monolayers (SAMs), fabricated from appropriate organothiols. The extent of lateral charge transport was investigated by insulating pre-defined patches within OSC-based SAMs with regions of insulating SAM made from large band gap alkanethiolates. The new method is demonstrated using a phenyl-linked anthracenethiolate (PAT), 4-(anthracene-2-ylethynyl)benzyl thiolate. I–V characteristics of differently shaped PAT-islands were measured using the AFM tip as a top electrode. We were able to determine a relationship between island size and electrical conductivity, and from this dependence, we could obtain information on the lateral charge transport and charge carrier mobility within the thin OSC layers. Our study demonstrates that AFM nanografting of appropriately functionalized OSC molecules provides a suitable method to determine intrinsic mobilities of charge carriers in OSC thin films. In particular, this method is rather insensitive with regard to influence of grain boundaries and other defects, which hamper the application of conventional methods for the determination of mobilities in macroscopic samples.
Keywords: conducting atomic force microscopy; lateral charge transport; nanografting; organic semiconductor; self-assembled monolayer

Molecular electronics: an introduction to theory and experiment - Cuevas, J. C.; Scheer, E. (World Scientific, 2017)

(untitled) - Nitzan, A.; Ratner, M. A. (Science, 2003)

(untitled) - Krupskaya, Y.; Gibertini, M.; Marzari, N.; Morpurgo, A. F. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Xu, X.; Yao, Y.; Shan, B.; Gu, X.; Liu, D.; Liu, J.; Xu, J.; Zhao, N.; Hu, W.; Miao, Q. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Karl, N.; Kraft, K.-H.; Marktanner, J.; Münch, M.; Schatz, F.; Stehle, R.; Uhde, H.-M. (J. Vac. Sci. Technol., A, 1999)

(untitled) - Cornil, J.; Calbert, J. P.; Brédas, J. L. (J. Am. Chem. Soc., 2001)

(untitled) - Cho, J.-m.; Higashino, T.; Mori, T. (Appl. Phys. Lett., 2015)

(untitled) - Podzorov, V. (MRS Bull., 2013)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Ulman, A. (Chem. Rev., 1996)

(untitled) - Vericat, C.; Vela, M. E.; Benitez, G.; Carro, P.; Salvarezza, R. C. (Chem. Soc. Rev., 2010)

(untitled) - Wold, D. J.; Frisbie, C. D. (J. Am. Chem. Soc., 2001)

(untitled) - Ishida, T.; Mizutani, W.; Aya, Y.; Ogiso, H.; Sasaki, S.; Tokumoto, H. (J. Phys. Chem. B, 2002)

(untitled) - Ditzler, L. R.; Karunatilaka, C.; Donuru, V. R.; Liu, H. Y.; Tivanski, A. V. (J. Phys. Chem. C, 2010)

(untitled) - Fang, L.; Park, J. Y.; Ma, H.; Jen, A. K.-Y.; Salmeron, M. (Langmuir, 2007)

(untitled) - Bumm, L. A.; Arnold, J. J.; Dunbar, T. D.; Allara, D. L.; Weiss, P. S. (J. Phys. Chem. B, 1999)

(untitled) - Blum, A. S.; Kushmerick, J. G.; Pollack, S. K.; Yang, J. C.; Moore, M.; Naciri, J.; Shashidhar, R.; Ratna, B. R. (J. Phys. Chem. B, 2004)

(untitled) - Ishida, T.; Mizutani, W.; Akiba, U.; Umemura, K.; Inoue, A.; Choi, N.; Fujihira, M.; Tokumoto, H. (J. Phys. Chem. B, 1999)

(untitled) - Fan, F.-R. F.; Yang, J.; Cai, L.; Price, D. W., Jr; Dirk, S. M.; Kosynkin, D. V.; Yao, Y.; Rawlett, A. M.; Tour, J. M.; Bard, A. J. (J. Am. Chem. Soc., 2002)

(untitled) - Yokota, Y.; Fukui, K.-i.; Enoki, T.; Hara, M. (J. Am. Chem. Soc., 2007)

(untitled) - Dubacheva, G. V.; Devynck, M.; Raffy, G.; Hirsch, L.; Del Guerzo, A.; Bassani, D. M. (Small, 2014)

(untitled) - Slowinski, K.; Chamberlain, R. V.; Miller, C. J.; Majda, M. (J. Am. Chem. Soc., 1997)

(untitled) - Bonhôte, P.; Gogniat, E.; Tingry, S.; Barbé, C.; Vlachopoulos, N.; Lenzmann, F.; Comte, P.; Grätzel, M. (J. Phys. Chem. B, 1998)

(untitled) - Inoue, A.; Mizutani, W.; Ishida, T.; Tokumoto, H. (Appl. Phys. A: Mater. Sci. Process., 1998)

(untitled) - Ramachandran, G. K.; Hopson, T. J.; Rawlett, A. M.; Nagahara, L. A.; Primak, A.; Lindsay, S. M. (Science, 2003)

(untitled) - Dauselt, J.; Zhao, J.; Kind, M.; Binder, R.; Bashir, A.; Terfort, A.; Zharnikov, M. (J. Phys. Chem. C, 2011)

Surface Science Techniques - Nefedov, A.; Wöll, C. (Advanced applications of NEXAFS spectroscopy for functionalized surfaces, 2013)

(untitled) - Käfer, D.; Bashir, A.; Dou, X.; Witte, G.; Müllen, K.; Wöll, C. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Bashir, A.; Heck, A.; Narita, A.; Feng, X.; Nefedov, A.; Rohwerder, M.; Müllen, K.; Elstner, M.; Wöll, C. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Liu, M.; Amro, N. A.; Liu, G.-y. (Annu. Rev. Phys. Chem., 2008)

(untitled) - Anthony, J. E. (Chem. Rev., 2006)

(untitled) - Aleshin, A. N.; Lee, J. Y.; Chu, S. W.; Kim, J. S.; Park, Y. W. (Appl. Phys. Lett., 2004)

(untitled) - Bock, C.; Pham, D. V.; Kunze, U.; Käfer, D.; Witte, G.; Terfort, A. (Appl. Phys. Lett., 2007)

(untitled) - Bashir, A.; Iqbal, D.; Jain, S. M.; Barbe, K.; Abu-Husein, T.; Rohwerder, M.; Terfort, A.; Zharnikov, M. (J. Phys. Chem. C, 2015)

(untitled) - Käfer, D.; Witte, G.; Cyganik, P.; Terfort, A.; Wöll, C. (J. Am. Chem. Soc., 2006)

(untitled) - Bashir, A.; Käfer, D.; Müller, J.; Wöll, C.; Terfort, A.; Witte, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Xu, S.; Liu, G.-y. (Langmuir, 1997)

(untitled) - Cygan, M. T.; Dunbar, T. D.; Arnold, J. J.; Bumm, L. A.; Shedlock, N. F.; Burgin, T. P.; Jones, L.; Allara, D. L.; Tour, J. M.; Weiss, P. S. (J. Am. Chem. Soc., 1998)

(untitled) - Zareie, M. H.; Ma, H.; Reed, B. W.; Jen, A. K.-Y.; Sarikaya, M. (Nano Lett., 2003)

(untitled) - Rosu, D. M.; Jones, J. C.; Hsu, J. W. P.; Kavanagh, K. L.; Tsankov, D.; Schade, U.; Esser, N.; Hinrichs, K. (Langmuir, 2009)

(untitled) - Ishida, T.; Mizutani, W.; Liang, T.-t.; Azehara, H.; Miyake, K.; Sasaki, S.; Tokumoto, H. (Ann. N. Y. Acad. Sci., 2003)

(untitled) - Karl, N.; Marktanner, J. (Mol. Cryst. Liq. Cryst. Sci. Technol., Sect. A, 2001)